2016
DOI: 10.3389/fnhum.2016.00407
|View full text |Cite
|
Sign up to set email alerts
|

Secular Slowing of Auditory Simple Reaction Time in Sweden (1959–1985)

Abstract: There are indications that simple reaction time might have slowed in Western populations, based on both cohort- and multi-study comparisons. A possible limitation of the latter method in particular is measurement error stemming from methods variance, which results from the fact that instruments and experimental conditions change over time and between studies. We therefore set out to measure the simple auditory reaction time (SRT) of 7,081 individuals (2,997 males and 4,084 females) born in Sweden 1959–1985 (su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…Decreasing the level of complexity in newly produced music should not increase turnaround, because even if it attracts more listeners initially, the number of listeners who lose interest should equal those who gain interest, and lead to the same net sales figures. An alternative explanation may be that general intelligence has decreased somewhat in Western populations during this period (e.g., Woodley and Figueredo, 2013 ; Woodley of Menie et al, 2015a , b ; Woodley of Menie and Fernandes, 2015 ; Madison et al, 2016 ), and that the industry is catering for the average cognitive processing ability in the largest consumer groups.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing the level of complexity in newly produced music should not increase turnaround, because even if it attracts more listeners initially, the number of listeners who lose interest should equal those who gain interest, and lead to the same net sales figures. An alternative explanation may be that general intelligence has decreased somewhat in Western populations during this period (e.g., Woodley and Figueredo, 2013 ; Woodley of Menie et al, 2015a , b ; Woodley of Menie and Fernandes, 2015 ; Madison et al, 2016 ), and that the industry is catering for the average cognitive processing ability in the largest consumer groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these studies examined parity progression to higher births and found that the intelligence differences were larger at higher parities. Recent studies on the US including have found small negative IQ-fertility gradients for men and women, with more consistent negative gradients for women (Lynn 1999, Lynn and Van Court 2004, Meisenberg 2010, Woodley et al 2016, though others have reported a small positive association for white men (Woodley and Meisenberg 2013).…”
Section: Previous Research On Intelligence and Fertilitymentioning
confidence: 99%
“…They have enabled very large-scale cross-national studies, of which the BBC Internet study of sex differences is perhaps the largest to date [17], featuring tests of mental rotation, object location memory, line angle judgement, and category fluency, all of which include some aspect of timing. However, the response times and time limits that these types of tests require are on the order of seconds, while reaction time tests, for example, require a resolution in the range of up to a few tens of milliseconds [18,19]. Here, we share the experience of a very large data collection of time-critical reaction time and time interval production data obtained from 7127 adult twins, sourced from the Swedish Twin Registry.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is conceivable that having and using an Apple or PC, laptop or smartphone, iOS or Android, and so forth, varies along the lines of age, sex, occupation, and so on. For example, reaction times increase with age and tend to be longer for women [18,44], and age and sex might therefore be confounded with the effects of platform per se. This phenomenon causes more severe problems than if the variation were merely random, as the demographic categories may, and are even likely to, co-vary with critical variables in the research design.…”
Section: Introductionmentioning
confidence: 99%